Influence Investment Opportunity Set, Leverage and Market Risk of Dividend Payout Ratio - Susanti, Neneng; Rahmayanti, Rima; Ramdan Padmakusumah, Rizal; R. , Achmad Drajat Aji Sujai (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine whether there is a significant influence on the investment opportunity set, leverage, and market risk against the partial dividend payout ratio and together. This research uses the descriptive method and verivikatif, a population drawn from manufacturing companies listed on the Stock Exchange for the 2012-2017 period. By using purposive sampling in the sampling. Source of data used secondary data that the financial statements of 15 manufacturing companies listed on the Stock Exchange for the 2012-2017 period. The analysis of the data used in this research is a multiple linear analysis with a significance level of 5%. The program used to analyze the data using E-Views 9. The results show that the partial investment opportunity set has a partial effect of the dividend payout ratio. and leverage has a partial effect on the dividend payout ratio. Market Risk While no effect partially on the dividend Ratio. And together indicate that the Investment Opportunity Set, Leverage and Market Risk significantly influence the Payout Ratio.